Alkaline electrolyte for zinc-air battery and preparation method of alkaline electrolyte

By using black bean extract as a corrosion inhibitor, the problem of self-corrosion of the zinc anode in zinc-air batteries in an alkaline environment is solved, improving battery performance and lifespan. The method is environmentally friendly and safe, and avoids the problems of traditional corrosion inhibitors. Toxicity and contamination issues.

CN119361921AInactive Publication Date: 2025-01-24INNER MONGOLIA UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411935885.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The self-corrosion of zinc anode in zinc air batteries in alkaline environments is serious, resulting in limited battery performance and life. Traditional corrosion inhibitors have problems such as high toxicity, pollution of the environment, high cost and complex synthesis.

Method used

Black bean extract is used as an environmentally friendly and safe corrosion inhibitor. Black bean fine powder is stirred in 6 M NaOH, and the filter residue is removed to obtain a solution containing black bean extract, which is used as an alkaline electrolyte for zinc-air batteries.

Benefits of technology

It effectively inhibits the self-corrosion of zinc in an alkaline environment, significantly reduces the corrosion rate of zinc anodes, improves Coulombic efficiency and anode utilization, extends battery life, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361921A_ABST
    Figure CN119361921A_ABST
Patent Text Reader

Abstract

The invention discloses an alkaline electrolyte for a zinc-air battery and a preparation method of the alkaline electrolyte, and relates to the technical field of zinc-air batteries, the preparation method of the alkaline electrolyte for the zinc-air battery comprises the following steps: S1, cleaning black beans with deionized water, drying, and grinding the black beans into black bean coarse powder by a grinder; s2, grinding the coarse black bean powder into fine black bean powder by using a mortar; s3, adding the black bean fine powder into 6M NaOH, stirring, and removing filter residues through vacuum filtration to obtain a solution containing a black bean extract; and S4, standing the solution containing the black bean extract for 25-35 minutes to obtain the alkaline electrolyte for the zinc-air battery, the black bean extract is used as the corrosion inhibitor, so that the electrochemical stability window of the electrolyte is widened, and the stability of the electrolyte is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc-air batteries, and in particular to an alkaline electrolyte for zinc-air batteries and a preparation method thereof. Background Art

[0002] With the growth of fossil fuel consumption and environmental concerns, clean and sustainable development technologies such as electrochemical devices and membrane bioreactors are very popular in the future renewable energy market. Zinc-air batteries are a type of metal-air batteries with high energy density and environmental friendliness. They have attracted widespread attention due to their potential high theoretical energy density, high theoretical capacity and simple electrochemical principles. Zinc-air batteries use metallic zinc as an anode and oxygen in the air as a cathode reactant to generate electricity through electrochemical reactions. Especially under alkaline electrolyte conditions, the redox reaction of zinc exhibits excellent electrochemical properties, making alkaline zinc-air batteries show great application prospects in energy storage devices, portable power sources and other fields. However, the self-corrosion problem of zinc anode in alkaline environments seriously restricts the performance and life of the battery.

[0003] In alkaline electrolytes, the zinc surface easily reacts with hydroxide ions to form zinc oxide or zinc hydroxide. These oxide and hydroxide layers not only hinder the effective electrochemical reaction, but also easily form a local battery effect, accelerating the corrosion process of zinc. In order to slow down the self-corrosion of zinc in an alkaline environment, the method of adding corrosion inhibitors is usually adopted. However, the commonly used traditional inorganic corrosion inhibitors and organic corrosion inhibitors have problems such as high toxicity, environmental pollution, high cost and complex synthesis, which seriously limit its large-scale application. Summary of the invention

[0004] Plant extracts are environmentally friendly, safe, readily available, non-toxic, biodegradable and renewable natural green electrolyte corrosion inhibitors. They are rich in compounds such as phenylpropanoids, flavonoids, tannins, amino acids, etc., which can serve as active centers to promote the adsorption of molecules on metal surfaces and inhibit metal corrosion. Based on this, the present invention provides a highly efficient environmentally friendly corrosion inhibitor, electrolyte and preparation method thereof, which solve the problems of high toxicity, environmental pollution, high cost and complex synthesis of existing corrosion inhibitors, and also solve the technical problems of hydrogen evolution corrosion and reduced Coulomb efficiency of zinc-air battery anodes under existing technical conditions, resulting in low anode utilization and fast corrosion rate, as follows: A method for preparing an alkaline electrolyte for a zinc-air battery comprises the following steps: S1: Wash the black beans with deionized water, dry them, and grind them into coarse black bean powder using a grinder; S2: Grind the black bean coarse powder with a mortar to obtain black bean fine powder; S3: taking black bean fine powder, adding it to 6 M NaOH and stirring it, removing the filter residue by vacuum filtration to obtain a solution containing black bean extract; S4: The solution containing the black bean extract is allowed to stand for 25-35 minutes to obtain an alkaline electrolyte for a zinc-air battery.

[0005] Furthermore, in step S1, the particle size of the black bean coarse powder is sieved through a 100-mesh sieve.

[0006] Furthermore, in step S1, the drying temperature is 50-60° C., and the drying time is 48-72 h.

[0007] Furthermore, in step S2, the particle size of the black bean fine powder is sieved through a 200-mesh sieve.

[0008] Furthermore, in step S3, 0.1-0.3 g of black bean fine powder is added into 100 ml of 6 M NaOH and stirred for 1-2 h.

[0009] Furthermore, in the alkaline electrolyte for zinc-air batteries, the concentration of black bean extract is 1 g / L-3 g / L.

[0010] Furthermore, in the alkaline electrolyte for zinc-air batteries, the concentration of black bean extract is 2 g / L.

[0011] On the other hand, the present invention provides an alkaline electrolyte for zinc-air batteries prepared by a method for preparing an alkaline electrolyte for zinc-air batteries.

[0012] The alkaline electrolyte used in zinc-air batteries can effectively inhibit the self-corrosion of zinc in an alkaline environment. The principle is as follows: In the zinc-air battery reaction, black bean extract contains a variety of bioactive compounds, such as soy bean phenol, polyphenol compounds, flavonoid compounds, etc. These substances are preferentially adsorbed on the surface of the zinc anode and produce a protective film, preventing water molecules from directly contacting the surface of the zinc anode, inhibiting the electrochemical corrosion reaction of the metal, and significantly enhancing the discharge performance and anode utilization.

[0013] The above one or more technical solutions of the present invention have the following technical effects: 1. The present invention adopts black bean extract as a corrosion inhibitor. The plant extract is an environmentally friendly, safe, easily available, non-toxic, biodegradable and renewable natural green electrolyte corrosion inhibitor, which solves the problems of high toxicity, environmental pollution, high cost and complex synthesis of traditional inorganic and organic corrosion inhibitors, is conducive to promoting the green and sustainable development of zinc-air batteries, broadens the electrochemical stability window of the electrolyte, and improves the stability of the electrolyte.

[0014] 2. The present invention uses black bean extract as a corrosion inhibitor. The black bean extract is rich in compounds such as phenylpropanoids, flavonoids, tannins, amino acids, etc. These compounds can serve as active centers to promote the adsorption of molecules on the surface of metallic zinc, thereby effectively inhibiting the self-corrosion of zinc in an alkaline environment.

[0015] 3. The corrosion inhibitor and alkaline electrolyte prepared by the present invention can significantly reduce the corrosion rate of the zinc anode in an alkaline environment, reduce anode hydrogen evolution corrosion, improve the Coulomb efficiency and anode utilization, help to extend the life of the zinc-air battery, and improve the overall performance of the battery.

[0016] 4. For the electrolyte provided by the present invention, when the concentration of the black bean extract solution is 2 g / L, the polarization resistivity reaches 94.7%, indicating that the black bean extract has extremely high efficiency as a corrosion inhibitor.

[0017] 5. The electrolyte provided by the present invention significantly reduces the hydrogen evolution rate and evolution volume, and the hydrogen evolution inhibition efficiency can reach up to 92.3%, which proves the effectiveness of black bean extract as a corrosion inhibitor in inhibiting zinc anode self-corrosion.

[0018] 6. The electrolyte provided by the present invention has a corrosion inhibitor added thereto, which can effectively protect the surface of the zinc anode of the battery, reduce the corrosion rate, and thus extend the service life of the battery.

[0019] 7. The discharge performance test of zinc-air battery shows that the battery prepared by using the electrolyte of the present invention has a higher specific capacity (432.97 mAh·g -1 ) and more stable discharge voltage, especially in the step discharge test at different current densities, the battery containing black bean extract showed a smaller voltage drop and a more stable voltage output, which indicates that the black bean extract not only improves the corrosion inhibition performance of the zinc anode, but also significantly improves the discharge performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A process for preparing alkaline electrolyte for zinc-air batteries; Figure 2 The open circuit potential curve of the three-electrode system assembled by Examples 1-3 and the comparative example; Figure 3 The AC impedance diagrams of Examples 1-3 and Comparative Example; Figure 4 Bode fitting graphs showing the variation of impedance of the electrochemical system of Examples 1-3 and the comparative example with frequency; Figure 5 Bode fitting graphs showing the relationship between the phase angle and the frequency of the electrochemical system of Examples 1-3 and the comparative example; Figure 6The Tafel curves of Examples 1-3 and Comparative Example are shown in FIG. Figure 7 The hydrogen evolution rate and hydrogen evolution inhibition efficiency diagram of Examples 1-3 and Comparative Examples; Figure 8 The optical microscope images of Example 2 and the comparative example, a is an optical microscope image of the metal zinc electrode immersed in the comparative example for 12 hours; b is an optical microscope image of the metal zinc electrode immersed in Example 6 for 12 hours; c is an optical microscope image of the metal zinc electrode; Fig. 9 The zinc-air battery assembled from Example 2 and the comparative example was subjected to a current density of 1 mAcm -2 The constant current discharge curve diagram below; Fig.10 The voltage curves of the zinc-air batteries assembled in Example 2 and the comparative example at different current densities. DETAILED DESCRIPTION

[0021] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0022] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0023] Example 1 A method for preparing an alkaline electrolyte for a zinc-air battery comprises the following steps: S1: Wash the black beans with deionized water, dry them, and grind them into coarse black bean powder using a grinder; S2: Grind the black bean coarse powder with a mortar to obtain black bean fine powder; S3: 0.3 g of black bean fine powder was added to 100 ml of 6 M NaOH and stirred, and the residue was removed by vacuum filtration to obtain a solution containing black bean extract; S4: The solution containing the black bean extract is allowed to stand for 35 minutes to obtain an alkaline electrolyte for a zinc-air battery.

[0024] Furthermore, in step S1, the particle size of the black bean coarse powder is sieved through a 100-mesh sieve.

[0025] Furthermore, in step S1, the drying temperature is 60° C. and the drying time is 72 h.

[0026] Furthermore, in step S2, the particle size of the black bean fine powder is sieved through a 200-mesh sieve.

[0027] Furthermore, in step S3, the stirring time is 2 h.

[0028] Furthermore, in the alkaline electrolyte for zinc-air batteries, the concentration of black bean extract is 3 g / L.

[0029] Example 2 A method for preparing an alkaline electrolyte for a zinc-air battery comprises the following steps: S1: Wash the black beans with deionized water, dry them, and grind them into coarse black bean powder using a grinder; S2: Grind the black bean coarse powder with a mortar to obtain black bean fine powder; S3: 0.1 g of black bean fine powder was added to 100 ml of 6 M NaOH and stirred, and the residue was removed by vacuum filtration to obtain a solution containing black bean extract; S4: The solution containing the black bean extract is allowed to stand for 25 minutes to obtain an alkaline electrolyte for a zinc-air battery.

[0030] Furthermore, in step S1, the particle size of the black bean coarse powder is sieved through a 100-mesh sieve.

[0031] Furthermore, in step S1, the drying temperature is 50° C. and the drying time is 48 hours.

[0032] Furthermore, in step S2, the particle size of the black bean fine powder is sieved through a 200-mesh sieve.

[0033] Furthermore, in step S3, the stirring time is 1 h.

[0034] Furthermore, in the alkaline electrolyte for zinc-air batteries, the concentration of black bean extract is 1 g / L.

[0035] Example 3 A method for preparing an alkaline electrolyte for a zinc-air battery comprises the following steps: S1: Wash the black beans with deionized water, dry them, and grind them into coarse black bean powder using a grinder; S2: Grind the black bean coarse powder with a mortar to obtain black bean fine powder; S3: 0.2 g of black bean fine powder was added to 100 ml of 6 M NaOH and stirred, and the residue was removed by vacuum filtration to obtain a solution containing black bean extract; S4: The solution containing the black bean extract is allowed to stand for 30 minutes to obtain an alkaline electrolyte for a zinc-air battery.

[0036] Furthermore, in step S1, the particle size of the black bean coarse powder is sieved through a 100-mesh sieve.

[0037] Furthermore, in step S1, the drying temperature is 55° C. and the drying time is 60 h.

[0038] Furthermore, in step S2, the particle size of the black bean fine powder is sieved through a 200-mesh sieve.

[0039] Furthermore, in step S3, the stirring time is 1.5 h.

[0040] Furthermore, in the alkaline electrolyte for zinc-air batteries, the concentration of black bean extract is 2 g / L.

[0041] Comparative Example The difference between this comparative example and Example 3 is that black beans were not added when preparing the electrolyte, which is specifically as follows: 24 g NaOH was weighed, dissolved in deionized water, cooled to room temperature, and diluted to a 100 mL volumetric flask to obtain 100 mL, 6 mol / L sodium hydroxide solution, i.e., the electrolyte (Blank).

[0042] Experimental Section In order to further verify the influence of the alkaline electrolyte for zinc-air batteries prepared by the present invention on the self-corrosion performance and discharge performance of the zinc anode, test examples 1-4 were respectively subjected to electrochemical tests, hydrogen evolution tests, discharge performance tests, and corrosion degree tests of metal zinc electrodes, among which industrial pure zinc with a purity of 99.99% was used as the zinc negative electrode of the alkaline zinc-air battery. Before the experiment, the surfaces were polished with 400, 800, 1500, and 2000 grit sandpapers in sequence, and then ultrasonically washed with anhydrous ethanol and deionized water in sequence, and then dried at room temperature. The specific test examples are as follows:

[0043] Test Example 1 The electrochemical performance test was performed on a CHI660E electrochemical workstation using a classic three-electrode system setup, including a 1 cm² zinc anode as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode with a Luggin capillary as the reference electrode. The test process is as follows: Open circuit potential (OCP) measurement: First, the zinc anode was immersed in the electrolyte and its open circuit potential change was recorded within 1000 seconds until the potential stabilized to obtain the steady-state open circuit potential.

[0044] Electrochemical impedance spectroscopy (EIS) analysis: Based on the steady-state open circuit potential, at 10 5 Hz to 10 -2An AC signal with an amplitude of 5 mV was applied in the frequency range of 10 Hz to perform EIS measurements. The impedance data obtained were analyzed using ZSimpWin software and an equivalent circuit model.

[0045] Tafel curve collection: Tafel curves were recorded in the range of ±250 mV relative to the stable open circuit potential at a scan rate of 1 mV / s.

[0046] The electrochemical performance tests of the electrolytes prepared in Examples 1 to 3 and the comparative example were carried out according to the above method.

[0047] The open circuit potential (OCP) results are shown in Figure 2. Due to the passivation reaction of the zinc anode, all open circuit potential curves move upward in the initial stage, and then the potential gradually reaches a stable state with the increase of immersion time.

[0048] The test results of electrochemical impedance spectroscopy (EIS) are as follows: Figure 3 As shown in the figure, this figure is an AC impedance diagram of 6 mol / L sodium hydroxide solution (blank sample) and black bean extracts at different concentrations. In the AC impedance diagram, the radius of the semicircle directly reflects the value of the transfer charge resistance (Rct) between the solution and the zinc interface. The larger the radius of the semicircle, the larger the Rct, which indicates a higher corrosion inhibition efficiency; on the contrary, if the radius of the semicircle is smaller, the Rct is smaller and the corrosion inhibition efficiency is lower. In order to quantify this corrosion inhibition effect, we use the following formula to calculate the corrosion inhibition efficiency (η):

[0049] in, R inh and R 0 R with and without corrosion inhibitor ct The results are shown in Table 1: Table 1 EIS fitting data

[0050] From Table 1, it can be concluded that the corrosion inhibition efficiency of the alkaline electrolyte for zinc-air batteries with the addition of 1 g / L, 2 g / L and 3 g / L black bean extract is 49.9%, 94.7% and 90.2% respectively. The corresponding Bode amplitude and phase angle diagrams are shown in Figure 4 , 5 , further verifying the characteristics of pure capacitive behavior.

[0051] Under the same conditions, when black beans were added to the electrolyte, the anode of the Tafel curve moved to the area with lower current density, indicating that the black bean extract was an anodic corrosion inhibitor that could inhibit the dissolution of the anode metal zinc. As the concentration of black beans gradually increased, the radius of the impedance ring in the AC impedance diagram also increased, reaching the maximum at a concentration of 2 g / L, indicating that the corrosion rate gradually decreased with the increase of black bean extract.

[0052] The Tafel curve test results of metallic zinc in 6 mol / L sodium hydroxide solution are as follows Figure 6 As shown, at the same time, after adding different amounts of black beans to the sodium hydroxide solution of the same concentration, the Tafel curve test was also carried out. The corrosion current density data obtained from the test was used to calculate the corrosion inhibition efficiency using the following formula: η i ), and the calculation results are shown in Table 2.

[0053]

[0054] in, i corr(0) and i corr(inh) They are the current density of the blank sample and the current density of the sample with corrosion inhibitor added. The calculation results are shown in Table 2: Table 2 Tafel curve data results of zinc electrode in Examples 1-3 and Comparative Example

[0055] After calculation, it can be concluded that the corrosion inhibition efficiency of alkaline electrolyte for zinc-air batteries is 45.6%, 89.8% and 86.4% respectively when 1 g / L, 2 g / L and 3 g / L of black bean extract are added; after adding biomass corrosion inhibitor for galvanized pipe of heat exchanger under the same conditions, the anode of Tafel curve moves to the area with lower current density, which indicates that black bean extract is an anodic corrosion inhibitor that can inhibit the dissolution process of anode metal zinc.

[0056] In summary, as shown in Table 1-2 and Figure 2-6 It can be seen that: with the increase of the concentration of black bean extract, the impedance spectrum radius increases, the polarization resistance increases, and the corrosion current decreases. At the same time, it can be seen that Example 2 (2g / L) is the best choice, and its corrosion inhibition efficiency can reach 94.7%.

[0057] Test Example 2 The electrolytes prepared in Examples 1-3 and Comparative Example were subjected to hydrogen evolution tests respectively. The hydrogen evolution rate was determined by the water displacement method. The zinc samples were immersed in the above electrolytes for 7 days and the exhaust was recorded. Figure 6-Figure 7 As shown, Figure 6 It is the hydrogen precipitation volume diagram of Examples 1-3 and Comparative Example, Figure 7 The hydrogen evolution rate and hydrogen evolution inhibition efficiency of Examples 1-3 and Comparative Examples are shown in FIG. Figure 6 It can be seen that in the presence of black bean extract, H 2 The precipitation volume is significantly reduced; Figure 7 It can be seen that with the increase of the concentration of black bean extract, the hydrogen evolution rate decreases, and the inhibition efficiency of hydrogen evolution can reach 92.3%.

[0058] Test Example 3 The metal zinc electrode was immersed in the electrolyte prepared in Example 2 and the comparative example for 12 hours for in-situ surface analysis to observe the surface changes of the metal zinc. An optical microscope was used to observe the surface morphology of the zinc anode. Figure 8 As shown, in the electrolyte of the comparative example, pitting corrosion occurred at the zinc anode, indicating that its corrosion rate was relatively high, while in the electrolyte of Example 2, the increase in pitting corrosion was significantly slowed down, indicating that the black bean extract effectively protected the surface of the zinc anode and reduced the corrosion rate.

[0059] Test Example 4 To verify the effect of electrolyte on the discharge performance of zinc-air batteries, button zinc-air batteries were assembled using the electrolytes of Example 2 containing black bean extract and the electrolytes of the comparative example without black bean extract. The discharge performance of zinc-air batteries was measured at 1, 2, 5, 10 and 1 mA cm -2 The step discharge curve under Figure 9-10 As shown, Fig. 9 The zinc-air battery assembled from Example 2 and the comparative example was subjected to a current density of 1 mAcm -2 The constant current discharge curve diagram below; Fig.10 The voltage curves of the zinc-air batteries assembled in Example 2 and the comparative example at different current densities.

[0060] from Fig. 9 It can be seen that the specific capacity of zinc metal in Example 2 reaches 432.97 mAh·g -1 The specific capacity in the comparative example is 282.5Wh kg -1 Compared with the comparative example, the specific capacity detection values ​​of Example 2 are significantly improved.

[0061] from Fig.10 It can be seen that Fig.10 The step discharge test was performed with the current density gradually increasing to 1, 2, 5, 10 and 1 mA cm -2 The discharge voltage drop of the battery containing black bean extract was smaller than that of the control group, and the voltage remained stable during each discharge time.

Claims

1. A method for preparing an alkaline electrolyte for a zinc-air battery, characterized in that: The steps include: S1: Wash the black beans with deionized water, dry them, and grind them into coarse black bean powder using a grinder; S2: Grind the black bean coarse powder with a mortar to obtain black bean fine powder; S3: taking black bean fine powder, adding it to 6 M NaOH and stirring it, removing the filter residue by vacuum filtration to obtain a solution containing black bean extract; S4: The solution containing the black bean extract is allowed to stand for 25-35 minutes to obtain an alkaline electrolyte for a zinc-air battery.

2. The method for preparing an alkaline electrolyte for a zinc-air battery according to claim 1, characterized in that: In the step S1, the particle size of the black bean coarse powder is sieved through a 100-mesh sieve.

3. The method for preparing an alkaline electrolyte for a zinc-air battery according to claim 1, characterized in that: In step S1, the drying temperature is 50-60° C. and the drying time is 48-72 h.

4. The method for preparing an alkaline electrolyte for a zinc-air battery according to claim 1, characterized in that: In the step S2, the particle size of the black bean fine powder is sieved through a 200-mesh sieve.

5. The method for preparing an alkaline electrolyte for a zinc-air battery according to claim 1, characterized in that: In step S3, the stirring time is 1-2 h.

6. The method for preparing an alkaline electrolyte for a zinc-air battery according to claim 1, characterized in that: In step S3, 0.1-0.3 g of black bean fine powder is added into 100 ml of 6 M NaOH and stirred.

7. The method for preparing an alkaline electrolyte for a zinc-air battery according to claim 1, characterized in that: In the alkaline electrolyte for zinc-air batteries, the concentration of the black bean extract is 1g / L-3g / L.

8. The method for preparing an alkaline electrolyte for a zinc-air battery according to claim 1, characterized in that: In the alkaline electrolyte for zinc-air batteries, the concentration of black bean extract is 2 g / L.

9. An alkaline electrolyte for zinc-air batteries prepared according to the method for preparing an alkaline electrolyte for zinc-air batteries according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Alkaline electrolyte composite corrosion inhibitor and application thereof

    CN117646217A

  • Butterfly valve including shaft-integrated gate plate and installation method thereof

    KR102745058B1

  • Method for inhibiting or reducing the risk of macular degeneration

    US6001368A

  • Method for determining total amount of soy isoflavones in food

    WO2024221478A1